2010
DOI: 10.1002/adma.200904006
|View full text |Cite
|
Sign up to set email alerts
|

High‐Performance Thin‐Film Transistors with DNA‐Assisted Solution Processing of Isolated Single‐Walled Carbon Nanotubes

Abstract: Controlling the morphology of single‐walled carbon nanotubes (SWNTs) is essential to realize their excellent device characteristics in electronics. DNA‐wrapped SWNTs provides an effective, scalable way to fabricate the super‐uniform networks of highly isolated, structure‐sorted SWNTs for thin‐film transistors (TFTs). The DNA‐SWNTs are easily formed into uniform, desired‐density networks of individual nanotubes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
65
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(65 citation statements)
references
References 35 publications
0
65
0
Order By: Relevance
“…The observed values of our fabricated devices, namely for both mobility and on/off ratio, are very good for solution-sorted sc-SWNT networks 20,50,51 . We anticipate that higher mobility could be attained on further optimization of the SWNT network morphologies, as well as the various dispersion conditions.…”
Section: Dispersion With Various Polythiophene Derivativesmentioning
confidence: 56%
“…The observed values of our fabricated devices, namely for both mobility and on/off ratio, are very good for solution-sorted sc-SWNT networks 20,50,51 . We anticipate that higher mobility could be attained on further optimization of the SWNT network morphologies, as well as the various dispersion conditions.…”
Section: Dispersion With Various Polythiophene Derivativesmentioning
confidence: 56%
“…Multi-walled carbon nanotubes (MWCNTs) with their unique structure and properties are well known for the wide range of potential applications, from composite materials to nanodevices [1][2][3][4][5][6]. Unfortunately, because of the strong intrinsic van der Waals attractions, MWCNTs have limited solubility in most organic and aqueous solvents.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] This series of techniques can provide the effective way to prepare the homogeneous network of absolutely isolated SWCNTs with the designed tube density in order to make it suitable for the semiconducting channel with high performance in SWCNT-TFTs. [ 10 ] The investigation of the transport property of TFTs using this length-sorted SWCNTs has clearly shown the importance of controlling the tube density slightly more than the percolation threshold estimated by the tube length, and ten times improvement in the on/off ratio in TFTs with the longer SWCNTs, as predicted by the theoretical study. [ 10 ] As the next step to clarify the effect of structural parameters on SWCNT-TFTs, in this work, we focus on the diameter, which refl ects the electronic state of the SWCNTs.…”
Section: Doi: 101002/adma201102806mentioning
confidence: 93%
“…[ 10 ] The investigation of the transport property of TFTs using this length-sorted SWCNTs has clearly shown the importance of controlling the tube density slightly more than the percolation threshold estimated by the tube length, and ten times improvement in the on/off ratio in TFTs with the longer SWCNTs, as predicted by the theoretical study. [ 10 ] As the next step to clarify the effect of structural parameters on SWCNT-TFTs, in this work, we focus on the diameter, which refl ects the electronic state of the SWCNTs. [11][12][13][14] The recent study on SWCNT-TFTs has suggested the postulate that the continuous paths of large-diameter and/or metallic SWCNTs in the semiconducting channel causes the high off-current.…”
Section: Doi: 101002/adma201102806mentioning
confidence: 93%
See 1 more Smart Citation